2014
DOI: 10.1021/je500657f
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibrium Data and Model Comparisons for H2S Hydrates

Abstract: Hydrogen sulfide is an exceptionally stable structure I (sI) gas hydrate forming guest molecule that is becoming increasingly prevalent in oil and gas production. However, phase equilibria data on pure hydrogen sulfide hydrate reported in the literature are relatively limited and inconsistent compared to other common hydrate formers such as methane or carbon dioxide. In this study, 61 hydrate phase equilibria measurements for sI hydrates containing hydrogen sulfide are reported in the temperature range from T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 25 publications
6
59
0
Order By: Relevance
“…Prior to the study, a PVTSim sensitivity analysis was performed to validate the theoretical model and ensure reliable predictions. Ward et al [28] studied the hydrate equilibrium phase of H 2 S experimentally and validated his work using PVTSim and reported that, PVTSim could be accurately used for H 2 S hydrate equilibrium phase studies. In addition, Sule and Rahman [29] predicted the hydrate equilibrium phase of natural gas in the presence of H 2 S and inhibitor (methanol) using PVTSim.…”
Section: S T R U C T U R E I S T R U C T U R E I I S T R U C T U R E Hmentioning
confidence: 95%
“…Prior to the study, a PVTSim sensitivity analysis was performed to validate the theoretical model and ensure reliable predictions. Ward et al [28] studied the hydrate equilibrium phase of H 2 S experimentally and validated his work using PVTSim and reported that, PVTSim could be accurately used for H 2 S hydrate equilibrium phase studies. In addition, Sule and Rahman [29] predicted the hydrate equilibrium phase of natural gas in the presence of H 2 S and inhibitor (methanol) using PVTSim.…”
Section: S T R U C T U R E I S T R U C T U R E I I S T R U C T U R E Hmentioning
confidence: 95%
“…After the complete hydrate formation as visualized by a pressure halt, the formed hydrate was then dissociated by increasing the temperature stepwise by 0.2 K increments. An example of a pressure-temperature profile for liquid water-hydrate-H 2 S (g) and liquid water-hydrate-H 2 S (l) phase boundaries experiments, their results, and a more detailed explanation of the experimental work can be found elsewhere [13,22]. After the completion of each measurement, the H 2 S is released to (a) a dry gas trap, (b) a primary KOH scrubber, (c) a secondary KOH scrubber and (d) a final dry gas trap.…”
Section: Methodsmentioning
confidence: 99%
“…The point at which the slope of the P-T curve sharply changed was considered as the hydrate dissociation point. 32,34,35 2.4.2. Dynamics.…”
Section: Experimental Apparatusmentioning
confidence: 99%